2014
DOI: 10.3109/09687688.2014.960493
|View full text |Cite
|
Sign up to set email alerts
|

The arginine-facing amino acid residue of the rat aquaporin 1 constriction determines solute selectivity according to its size and lipophilicity

Abstract: Aquaporins (AQP) are transmembrane channels for small, predominantly uncharged solutes. Their selectivity is partly determined by the aromatic/arginine constriction. Ammonia is similar in size and polarity to water, yet a subset of aquaporins distinguishes between the two. We mutated the constriction of water-selective rat AQP1 to mimic that of the ammonia-permeable human AQP8 by replacing Phenylalanine 56 with histidine, Histidine 180 with isoleucine, and Cysteine 189 with glycine, alone and in combination. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Water molecules pass through the hydrophilic aquapore of each monomer in single file. Selectivity is conferred by two conserved asparagine-proline-alanine (NPA) motifs located at the centre of the monomer and an aromatic/arginine (ar/R) constriction that forms the narrowest part of the channel (Tajkhorshid et al, 2002;Krenc et al, 2014). As a linear molecule with a diameter similar to that of water, CO 2 is expected to be capable of passing through the aquapores, although the ar/R constriction poses a significant barrier to CO 2 movement (Hub and de Groot, 2006;Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water molecules pass through the hydrophilic aquapore of each monomer in single file. Selectivity is conferred by two conserved asparagine-proline-alanine (NPA) motifs located at the centre of the monomer and an aromatic/arginine (ar/R) constriction that forms the narrowest part of the channel (Tajkhorshid et al, 2002;Krenc et al, 2014). As a linear molecule with a diameter similar to that of water, CO 2 is expected to be capable of passing through the aquapores, although the ar/R constriction poses a significant barrier to CO 2 movement (Hub and de Groot, 2006;Wang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic central pore appears to provide an energetically more favourable route for CO 2 movement (Hub and de Groot, 2006;Wang et al, 2007). Ammonia resembles water in size and polarity and should be able to move through the aquapores, but does not permeate through the ar/R constriction as efficiently as water (Krenc et al, 2014). Given that the substrate specificity of zebrafish aquaporins in general is similar to that of their tetrapod counterparts (Tingaud-Sequeira et al, 2010), it is likely that CO 2 and ammonia traverse zebrafish AQP1a1 through pathways similar to those predicted for AQP1 from other species.…”
Section: Discussionmentioning
confidence: 99%
“…The location in the protein as well as the amino acid composition are reminiscent of the AQP selectivity filter, i.e., the ar/R constriction [23], where a positively charged arginine residue is situated in a hydrophobic, aromatic environment. The AQP selectivity filter restricts passage by size exclusion yielding water-specific channels (< 2.4 A diameter) [19], and AQPs with solute permeability, such as glycerol or urea (> 3.2 A) [23,[25][26][27][28][29][30].…”
Section: Structure Analysis Hints At a Size-selective Fnt Substrate Fmentioning
confidence: 99%
“…[18][19][20] Overall, all these studies have confirmed and extendedt he early sequence-based "hourglass"m odel. [22] Underneath, the pore centre is defined by two highly conserved asparagine-proline-alanine (NPA) motifs contained in the Ba nd El oops and semi-helices, whicha re responsiblef or exclusion of charged solutes. Close to the extracellular side, the aromatic/arginine selectivity filter (ar/R SF), the narrowestp oint of the pore, is responsible for size-exclusion of molecules.…”
mentioning
confidence: 99%
“…Close to the extracellular side, the aromatic/arginine selectivity filter (ar/R SF), the narrowestp oint of the pore, is responsible for size-exclusion of molecules. [22] Underneath, the pore centre is defined by two highly conserved asparagine-proline-alanine (NPA) motifs contained in the Ba nd El oops and semi-helices, whicha re responsiblef or exclusion of charged solutes. [23][24][25][26][27][28] Since the first crystal structure [15] and molecular dynamics (MD) simulations [18] were obtained, water transport through AQPs has been understood to occur as as ingle-file mechanism.M Ds tudies have helpede lucidating the role of the selectivity filters and their effects on permeation of water and other small uncharged solutes.…”
mentioning
confidence: 99%